Investigation into the Relationship between Spermidine Degradation and Phenolic Compounds Biosynthesis in Barley Seedlings under Ultraviolet B Stress - Chong Xie; Yahui Zhu; Chaoqun Leng; Qiaoe Wang; Pei Wang; Runqiang Yang (Plants, 2023)
Barley germination under ultraviolet B (UV-B) illumination stress induces effective accumulation of phenolic compounds in the barley. Spermidine can enhance the biosynthesis of phenolic compounds and alleviate the oxidative damage caused by UV-B. To better understand the function of spermidine, inhibitors of enzymes that are involved in the degradation of spermidine and the synthesis of gamma-aminobutyric acid (GABA), the product of spermidine degradation, were applied to barley germinated under UV-B treatment. The results showed a more severe oxidative damage, and a decrease in phenolic acid contents were observed when spermidine degradation was inhibited. However, GABA application did attenuate an increase in electrolyte permeability and MDA content caused by UV-B induced oxidative damage and improved the respiration rate. Meanwhile, GABA application can elevate the accumulation of phenolic compounds by ca. 20%, by elevating the activities of some key enzymes. Furthermore, the application of GABA, together with the inhibitor of spermidine degradation, can alleviate its suppression of the synthesis of phenolic acids, and resistance to UV-B stress. In conclusion, spermidine alleviated oxidative damage and enhanced the accumulation of phenolic compounds using its degradation product.